The Effect Of Maceration Extract And Sonication Extract Of Seeds Areca Nut ( Areca Catechu L.) On Antioxidant Activity On Dpph Free Radicals ( 1,1-Diphenyl-2-Picrylhydrazyl ) - Ag. Kirwanto; Susilo Y; Ronal T (CV. ULIL ALBAB CORP, 2025)
Free radicals are relatively unstable molecules, having one or more unpaired electrons in their outer orbitals. These molecules are reactive in the emergence of various diseases such as inflammation, atherosclerosis, cancer and premature aging. The activity of these radicals can be inhibited by the work of antioxidants. Areca nut seeds are proven to contain phenolic compounds and have activity as free radical scavengers . This research is an experimental study because an experiment was conducted on the samples used, namely areca nut seeds. The results of the antioxidant activity test showed that the IC 50 value of the sonication extract was smaller than the maceration extract. Therefore, when compared with the IC 50 category table, the sonication extract is included in the group of substances that have stronger antioxidant activity than the maceration extract. This is indicated by the IC 50 value of 97.34 ppm which is classified as strong in the IC 50 category table. While the IC 50 value of the maceration extract is 145.063 ppm which is included in the medium category. However, the IC 50 values of both extracts are still far from the IC 50 value of vitamin E which is classified as a very strong antioxidant with an IC 50 value of 0.514 ppm.